Does Live Stream Selling Affect Customer Engagement and Purchase Intention? The Shopee Live Platform Case Study - Arisman, Arisman; Salehudin, Imam (ASEAN Marketing Journal, 2022)
Manuscript type: Empirical paper Research Aims: The purpose of this paper is to investigate how customer shopping values (utilitarian, hedonic, and symbolic) influence customer trust, engagement, and purchase intention for live stream selling on e-commerce marketplace platforms. Design/methodology/approach: The information was gathered online from 225 valid respondents. Respondents are Shopee users from Indonesia who have watched Shopee Live stream selling within the last two weeks. The data was analysed using Structural Equation Modelling (SEM) with LISREL 8.51. Research Findings: The findings revealed that only symbolic value affects purchase intention, both directly and indirectly, whereas hedonic value affects purchase intention directly. Utilitarian value influences purchase intent indirectly through product trust and customer engagement. Theoretical Contribution/Originality: This study adds to the body of knowledge about online commerce by expanding on previous research on live stream selling, particularly by small sellers on Indonesian e-commerce platforms. Practitioner/Policy Implication: According to the findings of this study, small sellers doing Live Stream selling should focus on symbolic and hedonic value to increase customer purchase intention. Research limitation/Implications: The study's respondents may only represent some of the population of Indonesian online shoppers. Future research could consider balancing the types of respondents. In addition to enhancing the insight, the research model could be expanded by including additional antecedents or moderators.